2013
DOI: 10.1038/cddis.2013.343
|View full text |Cite
|
Sign up to set email alerts
|

P2X7 purinoceptors contribute to the death of Schwann cells transplanted into the spinal cord

Abstract: The potential to use Schwann cells (SCs) in neural repair for patients suffering from neurotrauma and neurodegenerative diseases is well recognized. However, significant cell death after transplantation hinders the clinical translation of SC-based therapies. Various factors may contribute to the death of transplanted cells. It is known that prolonged activation of P2X7 purinoceptors (P2X7R) can lead to death of certain types of cells. In this study, we show that rat SCs express P2X7R and exposure of cultured S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 44 publications
5
20
0
Order By: Relevance
“…Previous studies have presented evidence that P2X7R are expressed in the paranodal membrane of rat Schwann cells in vivo [15], in cultured mouse Schwann cells [8,21,24], in longitudinal sciatic nerve sections of rat and mouse [20] and in cross and longitudinal sciatic nerve sections of mouse [12]. In this study, we clearly demonstrate localization of P2X7R ir in two types of Schwann cells in longitudinal sciatic nerve sections.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Previous studies have presented evidence that P2X7R are expressed in the paranodal membrane of rat Schwann cells in vivo [15], in cultured mouse Schwann cells [8,21,24], in longitudinal sciatic nerve sections of rat and mouse [20] and in cross and longitudinal sciatic nerve sections of mouse [12]. In this study, we clearly demonstrate localization of P2X7R ir in two types of Schwann cells in longitudinal sciatic nerve sections.…”
Section: Discussionsupporting
confidence: 76%
“…Previous data has shown that the Schwann cells mainly express P2X7R [20,21,24]. Early electrophysiological and pharmacological data showed that P2X7R are functionally expressed in myelinating Schwann cells of peripheral nerves [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, inhibition of the P2X7R offers protection against ATP-mediated cell death in a number of cells expressing the P2X7R [12], [30], [36]. Therefore, C23, C40 and C60 compounds were finally tested for their effectiveness in preventing ATP-induced cell death in hP2X7R-expressing HEK293 cells to provide further supporting evidence for their action on the hP2X7R.…”
Section: Resultsmentioning
confidence: 99%
“…Schwann cells(Luo et al, 2013) and oligodendrocytes(Matute, 2011) that myelinate, respectively, peripheral and central neurones, also possess P2X 7 receptors. In Schwann cells P2X 7 receptors are involved in control of myelination in development(Faroni et al, 2014).…”
mentioning
confidence: 99%